THE EFFECTIVENESS OF VALUE CLARIFICATION TECHNIQUE LEARNING MODEL IN IMPROVING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS POST PANDEMIC - Yusrizal, Yusrizal; Hariati, Emy (Teunuleh Publisher, 2022)
This study aims to analyze the effectiveness of the Value Clarification Technique learning model in improving the character of post-pandemic elementary school students. This research was conducted at PAB 16 Klambir V Private Elementary School, Hamparan Perak District with a total sample of 40 fifth grade students. This type of research is a quasi-experimental method by comparing the Value Clarification Technique learning model with conventional learning models. Collecting data in this study through a questionnaire of student character development. Hypothesis testing is done by testing the independent sample t-test. Based on the results of the study, it was found that the character development of students who were taught with the Value Clarification Technique learning model was higher than the conventional learning model. In other words, the Value Clarification Technique learning model is very effectively used to improve the character of elementary school students, especially in post-pandemic learning